Analysis of the Hadith “Man Anzara Mu‘siran Au Wada‘a ‘Anhu” and Its Relevance to Online Loans: A Tahlili Approach in Islamic Finance - Hayatun Najah; Mashur Mashur; Viki Junianto (Lembaga Yasin AlSys, 2026)
The development of digital financial technology has expanded online lending services by providing easier public access to financing; however, online lending practices in Indonesia continue to face ethical and legal concerns, including riba, excessive interest rates, ambiguous contracts, and intimidating or inhumane debt collection methods. This study aims to analyze the authenticity of the hadith Man anzhara mu‘siran aw wada‘a ‘anhu and examine its relevance to online lending practices from an Islamic financial perspective. A qualitative approach was employed using the tahlili method through library research. Data were obtained from primary hadith sources, including Sahih Muslim, Sunan al-Tirmidhi, Sunan Ibn Majah, and Musnad Ahmad, as well as relevant hadith and Islamic finance literature. The analysis was conducted through takhrij of the hadith, criticism of sanad and matan, and contextual analysis of contemporary online lending practices. The findings show that the hadith is categorized as sahih li ghairihi and contains ethical values of compassion, tolerance, justice, and leniency toward individuals experiencing economic hardship. The study also finds that online lending practices involving riba, economic exploitation, and coercive debt collection contradict Sharia principles and the ethical values embedded in the hadith. The study concludes that the hadith is relevant as a normative foundation for developing a fair, transparent, and Sharia-compliant digital financial system. These findings contribute to Islamic finance discourse by strengthening the ethical basis for regulating online lending practices in accordance with maqasid al-Shari‘ah.